Процесуальні особливості участі захисника як учасника кримінального провадження - Єрохін, В. В.; Yerokhin, V. V.; Юхно, О. О.; Yukhno, O. O.; Олександр Юхно (Право і безпека. - 2014. - № 4 (55). - С. 109-113, 2014)
З урахуванням чинного кримінального процесуального законодавства України та практики його застосування розглянуто особливості участі захисника у кримінальному провадженні. Зосереджено увагу на статусі та процесуальних повноваженнях захисника. Зазначено, що чинним Кримінальним процесуальним кодексом України чітко не закріплені права захисника, у зв’язку з чим запропоновано внести зміни та доповнення з цього питання.

The specific features of lawyer’s participation in criminal proceedings according to the current criminal procedural legislation of Ukraine and practice of its usage are analyzed. It is noted that the lawyer is able to provide expert legal assistance in criminal proceedings. This provision is consistent with international regulations and the Constitution of Ukraine. In this regard it is noted on the status and procedural powers of the lawyer. It is stated that the current Criminal Procedural Code of Ukraine expressly enshrined the rights of defender and not gave him independence in carrying out its activities, and therefore proposed to amend this question. It was concluded that implementing protection feature, a lawyer does not allow the prosecution to deviate from the legislated decision-making and execution proceedings. It is noted that the reform of the criminal justice of Ukraine, carried out by the state, should include not only the adoption of new laws or amendments and additions to the existing, but also a comprehensive study of law enforcement provisions that will enable work out scientific and reasonable suggestions and recommendations for optimization and efficiency activities.

С учётом действующего уголовного процессуального законодательства Украины и практики его применения рассмотрены особенности участия защитника в уголовном производстве. Сосредоточено внимание на статусе и процессуальных полномочиях защитника. Отмечено, что действующим Уголовным процессуальным кодексом Украины четко не закреплены процессуальные права защитника, в связи с чем предложено внести изменения и дополнения по этому вопросу.
Procedural features of a lawyer as a member of the criminal proceedings
Процессуальные особенности участия защитника как участника уголовного судопроизводства
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; учасники кримінального процесу; участники уголовного процесса; participants of the criminal proceedings; кримінальне провадження; уголовное производство; criminal proceedings; захисник; защитник; attorney; адвокат